Modelo de avaliação da poluição atmosférica devido ao fluxo de veículos em cidades de pequeno porte - Gomes, Viviani Antunes (2008)
This work is aimed at finding a model that allows to forecast rates of air pollution in cities to small because the flow of vehicles based on the generation of scenarios and in comparison with the current situation. Initially, it was diagnosing the current situation of the study area (year 2007), based on a count of vehicles classified volume, operating conditions and traffic information in the public transport system in the area under study. The data collected were released in the Traffic Simulation Software Integrated System (TSIS), the animation and dynamic set, therefore, the current scenario in the study area. Then, three other scenarios were generated containing proposals with changes in search of better operating performance and emission levels of air pollutants minimized. The program TSIS shown to be of great value in the composition of the scenarios in this work to enable the simulation and analysis of likely future scenarios. The results showed that more possible reduction of around 6.7% on fuel consumption and expected 6.5% in average. In addition, the reorganization implemented in public transport moving part of the bus lines to another avenue with good characteristics of operation, we obtained a reduction of 5.3% in vehicles moving in the area. Thus, to allow the simulation of likely future scenarios, resulting from implementation of such solutions, or that traffic and its control, the TSIS provide subsidies for planning the movement of the vehicle fleet in small-sized cities, where the impossibility of allocating more substantial investment by governmental agencies would be offset by a rational use of the instrumentality of the program.